ORTAOKUL 6, 7 VE 8. SINIF ÖĞRENCİLERİNİN SÖZLÜKLERE YÖNELİK TUTUMLARI: BETİMSEL BİR ANALİZ. - YAMAN, Havva; DAĞTAŞ, Abdullah (Electronic Turkish Studies)
Dictionaries are comprised of words which are involved in the language of a nation and are the most apparent evidence of that a nation is existing in the history stage, thus they protect words and give information to its users about semantic values of words. Dictionaries also provide expanding of users' vocabularies by entraining different words and notions to their vocabularies. Consequently, they help expanding of their semantic world which is the basis of thinking. Accordingly, positive and negative attitudes of secondary school students to be developed towards dictionaries are quite important on dictionary using habits of them. Positive attitudes of students to be developed towards dictionaries shall enable taking more advantage of dictionaries and learning dictionary use as a skill. On the contrary, negative attitudes of students to be developed towards dictionaries shall cause disliking and unwillingness in using dictionaries. This study has been realized in order to determine whether attitudes of secondary school 6th, 7th and 8th class students towards dictionaries differ according to different variables or not. Totally 14215 6, 7 and 8 class students existing in 54 secondary school in central of İzmit comprises the population of this study. 1160 secondary school 6, 7 and 8 class students in 14 secondary schools who were chosen out of 14215 with "stratified sampling method" comprises the sample of the study. Quantitative screening model based on description has been used in this study. Data of the study has been collected with Personal Information Form by using Attitude Scale Directed Towards Dictionaries which are developed by Yaman and Dağtaş (2013). Collected data has been analyzed by using SPSS 15.0 (Statistical Package for Social Sciences) program. As the result of this study it is determined that attitudes of students towards advantages of using dictionary is medium-level and attitudes of them towards dictionary use is high level.